Students as partners in an Australian medical program: Impact on student partners and teachers - Pereira, Jarett Vanz-Brian; Vassil, John Christopher; Thompson, Rachel Elizabeth (International Journal for Students as Partners, 2020)
In this article, we will discuss and analyse the implementation of a Students-as-Partners (SaP) initiative in a formal medical curriculum. Effective student-staff collaboration led to the development of student-centred lessons that were relevant and engaging, while improving student-staff relationships. In addition, student partners developed leadership and management skills, gained knowledge about educational pedagogies, and acquired metacognitive strategies to improve personal learning. Our experience highlights the important role that medical students can play in driving educational innovation and the immense potential for SaP initiatives to benefit students and staff.